A retrospective evaluation of the Brain and Body Fitness Studio service on functional capacity and quality of life in people with neurological disorders - Ramos, Joyce S.; Chakraborty, Ranjay; Dalleck, Lance C.; Sarunic, Kristina; Khadka, Jyoti; Haslam, Tayla; Nassaris, Olivia (Frontiers in Neurology, 2023)
Background People with neurological disorders (ND) are less physically active than the general population due to physical, sensory, and/or cognitive impairments. These individuals often feel intimidated to join mainstream health and wellness centres due to lack of specialised support for people with ND. The Brain and Body Fitness Studio (BBFS) is one of the first Accredited Exercise Physiologist-led interprofessional services in Adelaide South Australia to provide individualised evidence-based multimodal exercise prescription and social support for this population. This comprehensive retrospective study evaluated the impact of BBFS on functional capacity (FC) determined as the six-minute walk distance (6MWD) achieved during a six-minute walk test (6MWT), of its members with ND. Methods Sixty-two BBFS members (age, 66 ± 10 years; 60% male) with ND (85% Parkinson’s Disease; average time since diagnosis, 4 years [IQR, 2 to 12 years]) and complete pre- and post-6-month clinical assessment of the primary outcome of the study, the 6MWD, were included in this retrospective analysis. A series of sub-analyses were also performed to investigate the effects of adherence to the recommended prescription of at least twice a week in the program (≥80%vs<80% adherence), and disease stage (time since diagnosis; ≥6vs<6 years) on FC. Results Although there was no statistically significant change in 6MWD from pre- to post-6-month BBFS program (+15±90 m, p=0.19), a clinically meaningful improvement of >14m was evident. Improvement in 6MWD was significantly greater in members who attended at least 80% of the recommended visits (≥80% visits, +37±58m; ≤80% visits, -1±105m, p=0.046). We also found a 6MWD improvement from pre- to post-6 months in those in the early years of their ND (<6 years since diagnosis, +39±76 m), but not in those in the later years of their ND (≥6 years since diagnosis, -36±123 m, between group difference, p=0.029). Conclusion A clinically meaningful 6MWD improvement may be elicited by services provided by BBFS in people with ND. Overall, the benefits appear to be more evident in members who attended the BBFS for at least 80% of the recommended visits and those who were in the early stage of their ND diagnosis.